Reconstruction of The Regulations on Verification of The Applicant's Identity by Notaries in The Preparation of Authentic Deeds to Address The Legal Void Regarding The Use of Fake Identities - Kartika Kartika; Rineke Sara (CV. Green Publisher Indonesia, 2026)
The purpose of this study is to investigate the legal loopholes concerning the use of false identities in Indonesian notarial practice, as well as the legal provisions governing a notary’s verification of an appearer’s identity in the preparation of an authentic deed. Notaries are public officials authorized to prepare authentic deeds with perfect evidentiary force, as stated in Articles 1868 and 1870 of the Civil Code. In practice, verification of the appearer’s identity is a crucial aspect of ensuring the validity of a deed and providing legal certainty for the parties. However, the provisions concerning the identity verification mechanism under Law Number 2 of 2014 concerning the Position of Notary remain general in nature and do not regulate in detail the standard procedures for verifying an appearer’s identity, thereby potentially leading to identity misuse, such as the use of false identities or identities belonging to other persons in the preparation of deeds. This study analyzes laws and regulations, legal theory, and relevant literature using a normative juridical legal research method with statutory and conceptual approaches. The results of the study indicate a legal gap in the mechanism for verifying an appearer’s identity by a notary, which has the potential to create legal uncertainty and the risk of legal liability for notaries. Therefore, a more comprehensive reconstruction of legal regulations is needed by strengthening identity verification obligations, developing standard verification procedures, and utilizing the national population administration system to ensure the authenticity of the parties’ identities in the preparation of authentic deeds, thereby increasing legal certainty and legal protection in notarial practice.